Bioprospecção de microrganismos endofíticos isolados de Tabebuia spp. e Hymenaea courbaril e identificação da produção de metabólitos de interesse biotecnológico - Romano, Luis Henrique (Universidade Federal de São Carlos, 2014)
Microorganisms, such as those belonging to the groups of Penicillium, Bacillus, Paenibacillus, represent represent an important source for the production of bioactive metabolites with varied applications. The production of these substances is directly related to the culture media, as well as the available carbon and nitrogen sources, conditions of pH, temperature and agitation (gas exchange). Among the microbial groups most studied about the production of various interest metabolites are the fungi and bacteria that inhabit the interior of plants, the endophytics. Thus, the present study aimed to isolate and identify endophytics microorganisms from leaves of four species of Tabebuia spp. and Hymenaea courbaril and study the production of interest metabolites by the lineages found. The microbial activities were studied: antibiotic capability against Gram positive and Gram negative bacteria, antifungal, antibiotic resistance, enzyme production, antitumor activity and pigment production. Microorganisms that stood out due to production of antibiotics, cytotoxicity against tumor cells and pigment production. This study selected microorganisms based on their most relevant production, in this case, it was the antibiotics production, pigments production and cytotoxicity, they were cultured in larger scale aiming at the improvement of the production of metabolite chosen according to the results. The selected microorganisms were a bacterium identified as Paenibacillus terrae and a fungus identified as Penicillium minioluteum/Talaromyces minioluteus complex. The P. terrae proved producing bioactive metabolites against Staphylococcus aureus, Escherichia coli and Candida albicans, in addition to novel cytotoxic activity against HTC, and OVCAR8 SF295 tumor cells. This bacterium also showed unprecedented anti-Leishimania activity, acting against the promastigote form of the parasite. The isolated fungus proved producing a red pigment, in large quantities without cytotoxic, antifungal or antibacterial activity, favoring its industrials applications. Both selected microorganisms demonstrated potential for biotechnological and industrial applications, suggesting the viability of promising continuity of the work performed.
Keywords: Biotecnologia; Microorganismos endofíticos; Compostos bioativos; Diversidade microbiológica; Citotoxicidade; Cerrados; Endophytic microorganisms; Bioactive metabolites; Cytotoxicity; OUTROS